Ectopic acromegaly with tumoral range hyperprolactinemia and apoplexy with a dramatic regression of pituitary hyperplasia - Gupta, Ashish; Kasaliwal, Rajeev; Das, Liza; Sharma, Surendra Kumar; Kaur, Vaishali; Vasiljevic, Alexandre; Raverot, Véronique; Korbonits, Márta; Dutta, Pinaki (Frontiers in Endocrinology, 2024)
Acromegaly due to ectopic secretion of growth hormone-releasing hormone (GHRH) is a rare disorder. The signs and symptoms of ectopic acromegaly are indistinguishable from acromegaly due to a somatotroph adenoma. A 35-year-old female presented with secondary amenorrhea for 10 years, intermittent headache, and reduced vision in both eyes for 4 years which worsened over 4 months before presentation. She was also diagnosed with uncontrolled diabetes mellitus. On examination, she had coarse facial features, a fleshy nose, and acral enlargement. She had diminished visual acuity(left>right) and bitemporal hemianopia on perimetry. Biochemical investigations revealed elevated IGF-1: 588ng/ml (reference range, RR 100-242 74-196), markedly elevated basal growth hormone:>80 ng/ml (RR0.12-9.88), and hyperprolactinemia in the tumoral range:832ng/ml . MRI sella demonstrated a 22x30x34mm sellar-suprasellar mass with T2 hypointensity. Chest imaging revealed a 75x87x106mm left lung mass, which was found to be a well-differentiated neuroendocrine tumor (NET) on biopsy. Plasma GHRH levels were elevated: 38,088 ng/l (RR <250-300), and a diagnosis of ectopic acromegaly secondary to lung neuroendocrine tumor was considered.During workup, the patient developed in-hospital pituitary apoplexy, which improved with medical management. After left pneumonectomy her clinical features of acromegaly improved, diabetes underwent remission and there was a marked reduction in plasma GHRH and pituitary size. Histopathology was suggestive of a neuroendocrine tumor with immunohistochemistry positive for GHRH and negative for prolactin. Her final diagnosis was ectopic acromegaly due to GHRH secreting lung NET with pituitary somatotroph and lactotroph pituitary hyperplasia and apoplexy in the hyperplastic pituitary.